2018
DOI: 10.3389/fphar.2018.01170
|View full text |Cite
|
Sign up to set email alerts
|

Di’ao Xinxuekang Capsule, a Chinese Medicinal Product, Decreases Serum Lipids Levels in High-Fat Diet-Fed ApoE–/– Mice by Downregulating PCSK9

Abstract: Numerous risk factors are responsible for the development of atherosclerosis, for which an increased serum level of low-density lipoprotein cholesterol (LDL-C) is a driving force. By binding to the low-density lipoprotein cholesterol receptor (LDLR) and inducing LDLR degradation, proprotein convertase subtilisin/kexin type 9 (PCSK9) plays a key role in cholesterol homeostasis regulation. The inducement of PCSK9 expression is also an important reason for statin intolerance. The Di’ao Xinxuekang (DXXK) capsule e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…The development of atherosclerosis is modulated by disturbances of lipid metabolism, oxidative stress, etc (Rzepecka‐Stojko et al., 2017). Moreover, accumulating data show that, during atherosclerosis progression, hyperlipidemia is a critical issue (Qu et al., 2018). Furthermore, oxidative stress is discovered to be related to hyperlipidemia (Cheng et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The development of atherosclerosis is modulated by disturbances of lipid metabolism, oxidative stress, etc (Rzepecka‐Stojko et al., 2017). Moreover, accumulating data show that, during atherosclerosis progression, hyperlipidemia is a critical issue (Qu et al., 2018). Furthermore, oxidative stress is discovered to be related to hyperlipidemia (Cheng et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Hypercholesterolemia, defined by an overload of lipids, as well as an imbalance of lipoproteins, including low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C), acts as a driving force and plays a vital role in the development and progression of atherosclerosis. 51,52 Herein, the in vivo study showed that serum TC and LDL-C were significantly increased in ApoE −/− mice fed a HFD 53 (Fig. 8d, f), while serum HDL-C was decreased (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Among these, five low-risk studies [ 40 , 42 , 43 , 66 , 68 ] used the “random number table” in the assessment of sequence generation, seven high-risk studies [ 24 , 33 , 34 , 49 , 59 , 75 , 76 ] did not report the entry, and the remaining 48 studies had unclear detailed random methods. Although none of the studies mentioned random housing, the outcome measures in the 19 studies [ 20 , 23 , 26 , 27 , 29 , 30 , 34 36 , 38 , 41 , 45 , 46 , 48 , 50 , 52 , 59 , 73 , 75 ] were not influenced since the feeding conditions (such as temperature, lighting, and humidity) were described, and the bias was evaluated as low risk. The incomplete outcome data were detected in 27 high-risk articles [ 19 21 , 23 , 26 , 32 36 , 39 , 45 – 47 , 50 53 , 55 , 56 , 60 , 61 , 68 , 74 – 77 ] without any reason or appropriate method for describing the missing data, while 18 articles [ 22 , 24 , 25 , 27 – 31 , 38 , 41 , 49 , 54 , 57 , 64 , 70 72 , ...…”
Section: Resultsmentioning
confidence: 99%